Australia : Financial Sector Assessment Program-Technical Note-Insurance Sector: Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2019)
This technical note provides an update on the Australian insurance sector and an analysis of certain key aspects of the regulatory and supervisory regime. The note analyzes the practice in relation to selected Insurance Core Principles (ICPs) in the context of a wider discussion of key issues in regulation and supervision. Despite the negative impact of the low interest rate environment, the life insurance industry retains sufficient loss absorption capacity. The Australian Prudential Regulation Authority (APRA) has undertaken a comprehensive reform of prudential regulation while improving the consistency of the framework between life and general insurers. This focused review confirms that prudential regulation and supervision by APRA is reasonably conservative. The risk-based capital framework is reasonably conservative, which facilitates supervisory risk assessments. APRA has high technical capacity to conduct effective supervision. While there are some gaps in the regulatory regime, APRA seeks to address these through its supervisory process. The report recommends that APRA should expand and deepen its scrutiny of group activities, especially those entailing risky investments and material intragroup transactions.